2016
DOI: 10.1177/2050312115626731
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 allele and malondialdehyde level are independent risk factors for Alzheimer’s disease

Abstract: Background:The ε4 allele of Apolipoprotein E is involved in lipid metabolism. Oxidative stress produces an increase in lipid peroxidation that has been implicated in the pathogenic cascade in Alzheimer’s disease. This study estimated the effect of the ε4 allele, malondialdehyde and lipid levels on the risk for Alzheimer’s disease.Methods:A total of 41 control subjects and 73 patients with Alzheimer’s disease were recruited. The Apolipoprotein E genotype was determined by amplification of exon 4 of the Apolipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…While in case of control group, non-significant difference was reported between females and males group. This observation was similar from previous publications that reported significant differences not only in MDA levels but also in various oxidative stress biomarkers like protein oxidation and DNA oxidation (Schrag et al, 2013;Chang et al, 2014;Iova et al, 2014;López-Riquelme et al, 2016). Demented females had higher levels of malondialdehyde than males that might be due to their higher prevalence of vascular diseases and lipid disorder.…”
Section: Disucssionsupporting
confidence: 91%
See 3 more Smart Citations
“…While in case of control group, non-significant difference was reported between females and males group. This observation was similar from previous publications that reported significant differences not only in MDA levels but also in various oxidative stress biomarkers like protein oxidation and DNA oxidation (Schrag et al, 2013;Chang et al, 2014;Iova et al, 2014;López-Riquelme et al, 2016). Demented females had higher levels of malondialdehyde than males that might be due to their higher prevalence of vascular diseases and lipid disorder.…”
Section: Disucssionsupporting
confidence: 91%
“…These findings support the hypothesis that demonstrate the presence of E4 allele and decline antioxidant level with elevated lipid peroxidation are independent risk factors for dementia. and they are contribute to the pathogenic cascade in dementia by different pathways (Ihara et al, 2000;Zito et al, 2013;López-Riquelme et al, 2016). In conclusion, our study indicated that the APOE4 allele and oxidative stress are separated risk factor in the pathogenesis of dementia in the Saudi population.…”
Section: Disucssionmentioning
confidence: 55%
See 2 more Smart Citations
“…The homozygosity for the APOE ε4 allele, as a major genetic risk factor for LOAD, was shown to be an independent genetic factor that significantly increases the risk of EOAD [ 127 ]. But, unlike mutations in APP , PSEN1 and PSEN2 , the APOE ε4 allele was not considered a significant cause of EOAD and was only a risk factor [ 128 ].…”
Section: Introductionmentioning
confidence: 99%